Insider and Outsider, Community and Conflict: Elizabeth Cecil Wilson’s transnational experiences as a Progressive American woman educator - Rousmaniere, Kate (Historia y Memoria de la Educación, 2022)
This essay takes a feminist educational biographical approach to the transnational life and work of the American educator Elizabeth Cecil Wilson (1913-1994). Central to this interpretation is the way in which Wilson’s life exemplifies the concept of “internal exile” as a result of her transnational movements in China, Korea, and the United States. Wilson’s early experiences with internationalism, all-women’s education and American progressive education shaped her interpretation of her later work in educational administration, leading her to develop a unique perspective about being both an “insider” and an “outsider” in her world. Raised in a variety of close and strongly identified communities, in her later professional life she experienced a sense of isolation and displacement in the structured hierarchical environments of international organizations and American state school systems. Late in life, she articulated this challenge in feminism when she argued for women’s inclusion in formal educational leadership.